Kedudukan Dan Konsep-Konsep Sindhènan Tradisi Jawa Timur Surabayan - Sukesi Sukesi (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
This paper focuses on the East Java Sindhènan Surabayan with the problems namely what form of gending that requires Sindhènan; how is the position of sindhènan in the presentation of Surabayan East Javanese traditional music; and how is the view of the East Javanese musicians about the aesthetic aspects of East Javanese Surabayan Sindhènan presentation? To answer this problem the ethno-art approach is used. The research data is obtained through literature studies, observations, and interviews. The results show that East Javanese Surabayan gending that involve Sindhènan elements is gending which has a similar form with srepegan, ayak-ayakan, ketawang, ladrang, ketawang gending, and kethuk loro kerep composition in karawitan Surakarta style. East Javanese Surabayan gendhing that require the sindhènan are gecul (humorous) and gobyog (crowded). The East Javanese Sindhènan Surabayan text is dominated by a parikan, while senggakan, isèn-isèn, and wangsalan represent a 'new' development which is influenced by the Central Javanese sindhenan, especially the Surakarta style. The concept of ngepas and nungkak is a tendency to the treatment of East Java sindhenan Surabayan because it is considered in accordance with technique of tabuhan.Keywords: sindhènan, East Java Surabayan, Position, Concept